Immunogenic properties of the surface layer precursor of Clostridium difficile and vaccination assays in animal models. (February 2016) - Bruxelle, J.-F.; Mizrahi, A.; Hoys, S.; Collignon, A.; Janoir, C.; Péchiné, S.
Abstract: Clostridium difficile is an opportunistic pathogen causing gut inflammation generally associated with an intestinal dysbiosis due to antibiotics. Several virulence factors have been identified as playing a key role in gut colonization. The surface-layer proteins, comprised of two proteins, the high molecular weight SlpA (HMW-SLP) and the low molecular weight SlpA (LMW-SLP), are the most abundant proteins on the C. difficile surface. These two proteins are derived from the Cwp84-mediated cleavage of a single precursor protein SlpA. In this study, we assessed the immunogenic properties of a recombinant SlpA precursor derived from a toxigenic C. difficile strain (630) and its protective effect as a vaccine antigen co-administered with the cholera toxin as an adjuvant in both hamster and mouse models. First, we confirmed the immunogenicity of SlpA in humans. Sera from patients with C. difficile infection were analyzed by ELISA. Patients with CDI have a greater number of SlpA antibodies than healthy patients, confirming the immunogenicity of this protein during the pathogenic process. Then, rectal vaccination assays were performed in both conventional hamsters and mice. The animals' sera were sampled before and after vaccination, and were analyzed by ELISA. In addition, in the mouse model, feces were sampled after vaccination and IgA directed against SlpA were detected by ELISA. In both models, the intestinal colonization was evaluated by fecal bacterial count after challenge. Intra-rectal vaccination with SlpA and cholera toxin as an adjuvant induced a local and systemic humoral immune response in mice and hamsters potentially responsible for the weak decrease of C. difficile colonization in mice and the partial protection observed in a lethal-hamster model. Highlights: Clostridium difficile SlpA is immunogenic and is interesting as vaccine antigen. Vaccination with C. difficile SlpA induced partial protection in hamster. Mice vaccination with C. difficile SlpA led to a decrease gut colonization.